Achievements of Lithuanian sustainable development during the integration process into the European Union - Liobikienė, Genovaitė; Mandravickaitė, Justina (Technological and Economic Development of Economy, 2011)
After the collapse of the Soviet Union, Lithuania rapidly started turning towards European trade patterns averting from those of the former communist regime. However, European integration has had an effect not only on convergence of gross domestic product (GDP) but also on convergence of prices as well as on alteration of living standards. The goals of Lithuanian integration to the EU were noted in the National Lithuanian Sustainable Development Strategy. The key objective of sustainable development in Lithuania was to achieve the present developmental level of the EU countries according to indicators of economic and social development. Therefore, the paper compares the convergence across the old and newer member-states of the EU in terms of GDP, household final consumption expenditure and comparative price level indices. In addition, it is revealed that Lithuanian expenditure patterns rapidly approach those of the old member-states of the EU. Consequently, Lithuanian integration to the EU contributes to approaching the EU-15 level what means the successful achievements of Sustainable Development Strategy as well. So, the aim of this paper is to show how successful are Lithuanian sustainable development achievements in terms of GDP, comparative price level and household expenditure within framework of integration to the EU.